The Role of Islamic Religious Education Teachers in Shaping Multicultural Character in the Era of Generation Alpha at MA Ma'arif Roudlotut Tholibin Metro City - Yulia Rahma Nuraini; Dedi Setiawan; Mai Zuniati (Assyfa Journal of Islamic Studies, 2026)
This study aims to describe the role of Islamic Religious Education (PAI) teachers in shaping multicultural character among Generation Alpha students and to identify the multicultural values developed at MA Ma'arif Roudlotut Tholibin, Metro City. The research employs a qualitative approach with a case study design, where data were collected through in-depth interviews, participatory observation, and documentation. Participants were selected purposively, consisting of PAI teachers, tenth-grade students, the madrasah principal, and homeroom teachers, with data analysis following the interactive model of Miles, Huberman, and Saldaña. The findings reveal five strategic roles of PAI teachers (value educator, role model, cross-cultural dialogue facilitator, motivator, and evaluator) and seven internalized multicultural values (tolerance, justice, brotherhood, empathy, open-mindedness, democratic dialogue, and peace-loving). This study also identifies major challenges including exposure to intolerant digital content and individualistic tendencies among Generation Alpha students. The implications emphasize the need to integrate digital literacy into PAI learning as well as culturally responsive pedagogy training for teachers.